Exergetic Evaluation of an Avocado (laurus Persea L.) Biorefinery in Northern Colombia - Tamy C. Herrera-Rodriguez; Vianny Parejo-Palacio; Angel D. Gonzalez-Delgado (Chemical Engineering Transactions)
In Colombia, avocado cultivation is prominent in departments such as Bolívar, Antioquia, Tolima, Cesar, Caldas, Valle del Cauca, Quindío, and Santander, covering 86% of the planted area. In Bolívar, particularly in the Montes de María, avocados damaged by fungi, poor marketing, and deteriorated roads pose a challenge. This study proposes a biorefinery approach to valorize these wastes by producing oil, chlorophyll, biochar, fat-free pulp, and fertilizer. The research evaluates the overall exergy efficiency and identifies key thermodynamic irreversibilities in an avocado (Laurus Persea L) biorefinery in northern Colombia. Exergy, which measures energy quality and work potential, is used to assess process efficiency and sustainability. Results show that stages 8 (oil distillation, condensation, and refrigeration), 12 (pyrolysis and by-product separation), and 16 (chlorophyll extract distillation, condensation, and refrigeration) have the highest exergy destruction, accounting for 23.90 %, 33.27 %, and 7.84 %, respectively. The peel washing stage demonstrated high exergetic efficiency (97.32 %) due to its contribution to chlorophyll-rich extract and fertilizer production. However, stage 12 had significant exergy loss (2,438.52 MJ/h) because the volatile gases produced during pyrolysis were not utilized as biorefinery products. The highest irreversibilities were observed in stages 8 and 12. The overall exergy efficiency of the process was 46.26 %, higher than systems that use only avocado pulp, as this biorefinery integrates seeds and peels into its processes, reducing waste generation. This study highlights the potential of avocado crop residues for value-added production and emphasizes the need to optimize processes to enhance energy efficiency and sustainability.